DESIGN ANALYSIS OF CURRICULUM DEVELOPMENT OF PUBLIC SECTOR ACCOUNTING STUDY PROGRAM BASED ON INDEPENDENT CAMPUS LEARNING ON INDEPENDENT CAMPUS KUPANG STATE POLYTECHNIC - Hapsa Usman; Deetje Manuain; Nonce Farida Tuati (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2022)
Independent Campus is a program that has been launched by the government through the Ministry of Education and Culture, Research and Technology. There are four main points regarding the design of the Merdeka Campus: first, regarding the freedom to open new study programs for A and B accredited universities; second, re- accreditation is automatic for all ratings and can be proposed at any time; third, the freedom to form State Universities as Legal Entities from State Universities as Public Service Agencies and State Universities as Work Units; fourth, the rights given to students to engage in activities outside the study program and the change in the definition of credit from "study hours" to "hours of activity". In the fourth point, there is a choice of programs for students in the form of entrepreneurship activities. This activity in its design can be carried out by students for two semesters or 40 credits. This study aims to develop a curriculum development design for the Public Sector Accounting Study Program in accordance with the Independent Learning-Independent Campus (MBKM) program at the Kupang State85 Polytechnic. The method used in this research is the research and development method. The research stages are, the Introduction stage, the planning stage and the development stage. The population in this study is a limited population (Definite). The research instrument was carried out using a questionnaire. The data analysis technique used is descriptive analysis technique, namely = /N × 100% as the qualification level for the eligibility criteria to conclude the validation results. Based on the results of research based curriculum design Merdeka Learning- Independence Campus (MBKM), in the Public Sector Accounting Study Program developed in this study is feasible to use.